KORELASI POLA PANGGILAN PELAYANAN TOKOH-TOKOH ALKITAB DENGAN POLA PANGGILAN PELAYANAN MAHASISWA STT INJIL BHAKTI CARAKA BATAM - Manalu, Putri Natacya; Marbun, Pardomuan (CARAKA: Jurnal Teologi Biblika dan Praktika, 2024)
The call speaks of the invitation to salvation that God gives freely to mankind. God does not want humans to just experience repentance and receive salvation, but also to be involved in serving Him in the world in preaching the Gospel. God will even call someone to serve Him full time. This paper is a qualitative research study with a phenomenological approach to find a correlation between the patterns of calling to service of Bible figures and the patterns of calling of students at STT Evangeli Bhakti Caraka. This paper can hopefully help students to become more confident and firm in their vocation, and can also serve as reference material for theological colleges before accepting new students. Apart from that, this paper can broaden students' insight into calling patterns and also add to the literature in carrying out tasks related to calling. In this paper, it was found that knowing the correlation between the calling patterns of figures in the Bible and the calling patterns of students at STT Evangeli Bhakti Caraka actually had an impact, namely that students became more confident in their calling.